The Concept of Tawhid in the Perspective of Nusantara Mufassirs: A Comparative Study of Tafsir Al-Misbah and Tafsir Al-Azhar - Ramadhani, Dara; Taufiq, M. (IDRIS Darulfunun Institute, 2024)
Tawhid, as a fundamental concept in Islam, serves as the primary foundation for all religious teachings, particularly in the aspects of worship and social life. Tawhid not only teaches the oneness of Allah SWT but also acts as the basis that guides the behavior of Muslims in all aspects of their lives. Given the importance of this concept, various mufassirs or Qur'anic scholars from different cultural and intellectual backgrounds have sought to interpret it according to the context of their times and societies. This study focuses on two prominent mufassirs from the Nusantara, Quraish Shihab and Buya Hamka, whose works, Tafsir Al-Misbah and Tafsir Al-Azhar, have become key references in Islamic studies in Indonesia. The aim of this research is to compare and analyze how these two mufassirs understand and interpret the concept of Tawhid in the Qur'an. The method used is library research with a comparative approach, allowing the identification of similarities and differences in the interpretation of Tawhid by the two mufassirs. Tafsir Al-Misbah by Quraish Shihab is known for its contextual and modern approach, often linking the interpretation of Qur'anic verses to contemporary social realities. Conversely, Tafsir Al-Azhar by Buya Hamka tends to use a more traditional approach, emphasizing the relevance of Qur'anic teachings in the daily lives of Muslims. The findings reveal that, despite differences in interpretative methods, both mufassirs share similar views on the essence of Tawhid. Quraish Shihab emphasizes the importance of contextual understanding tailored to the challenges of the times, while Buya Hamka focuses more on the spiritual and moral aspects of Tawhid. This difference lies in their methods, with Shihab inclined toward a more flexible hermeneutic approach, whereas Hamka is more literal and normative. Nonetheless, both agree that Tawhid should be reflected in all aspects of a Muslim's life and serve as the foundation for all moral actions and worship. This research provides important insights into the interpretation of Tawhid by Nusantara mufassirs and its relevance in the lives of Muslims in Indonesia today.